2014
DOI: 10.18869/acadpub.jhs.2.2.52
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Health-Promoting Behaviors of Medical Sciences Students of Islamic Azad University of Sari, Iran 2013

Abstract: Background and purpose: Health-promoting activities and a healthy lifestyle are major strategies to preserve health. The purpose of this research study, health-promoting behaviors of medical sciences student of Islamic Azad University of Sari, Iran, was carried out in order to determine the compliance and to promote the medical community. Materials and Methods:This was a cross-sectional study conducted on 285 university students, School of Medical Sciences, Sari, Iran, who were selected using stratified random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Previous research has identified coronary heart disease as the first and most common cause of death in Iran. The mortality rate of coronary heart disease in Iran is high; approximately 300 people die every day due to the complications of this disease (Forouzanfar et al 2014;Mahmoodi et al 2014;Mohammadian-Hafshejani et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has identified coronary heart disease as the first and most common cause of death in Iran. The mortality rate of coronary heart disease in Iran is high; approximately 300 people die every day due to the complications of this disease (Forouzanfar et al 2014;Mahmoodi et al 2014;Mohammadian-Hafshejani et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Khazaee et al ( 18 ) and Hosseinin et al ( 19 ) also reported that these behaviors are undesirable and mediocre in the students of nursing and medicine. Other studies ( 20 – 22 ) stated that the mean score for health-promoting behavior was acceptable. The results of various studies have been reported in a range from adverse to acceptable which indicates a weakness in students’ health behaviors and their tendency toward hygienic behaviors.…”
Section: Discussionmentioning
confidence: 97%